Geopolitics of Laos Renewable Energy and the Development of Water Energy for the Integrated Southeast Asia's Electricity - Ramaldy Krisna Indradipradana; Bevita Sari (Journal of Asian Social Science Research, 2024)
This research explains the geopolitics of renewable energy from Laos as a country that has potential in water-based energy (hydropower) in the Southeast Asia region, with the main focus analyzing the mapping of the geopolitics of Laos renewable energy in the development of hydropower energy in Southeast Asia. The authors use the concept of Renewable Energy Geopolitics, which aims to map the geographic and technical characteristics of renewable energy systems and analyze energy relations between countries. The research method used is descriptive qualitative with literature study techniques in data collection. This research shows that Laos is taking advantage of competitive market conditions, thereby triggering investment in the water-based energy sector. Laos also focuses on producing water-based energy by implementing decentralization policies and community involvement in national development to minimize energy poverty, as well as organizing cooperation in technology to produce water-based energy with developed countries both from inside and outside the region.